THE PSYCHOGRAPHIC DIMENSIONS OF INVESTORS AND THEIR RISKY INVESTMENT CHOICE - Kanagasabai, Balaji; Aggarwal , Vaneeta (International Journal of Psychosocial Rehabilitation, 2020)
The main aim of this research study is to find the relationship between the investors’ significant psychographic dimension, personality typology and risky investment choices. The Bailard, Biehl and Kaiser five- way model factors are used as the independent variables for this study and the dependent variable is the risky investment choice. Data are collected from postgraduate finance students and analysed using JASP. The findings reveal that the adventurer and celebrity investors are having a significant and positive relationship with the risky investment choice. This study is useful for individual investors to understand themselves, financial advisors to design the portfolio according to the psychographic nature of the clients.